Determinants of adoption of integrated soil fertility management practices among coffee producers in Mid-Northern Uganda - Alela, Beatrice; Katya Kule, Enos; Midamba, Dick Chune; Mugonola, Basil (Cogent, 2024)
Coffee accounts for over 40% of total Ugandan exports. Coffee subsector created employment opportunities thus improved living standards of farmers. Despite significant role played by coffee, its production in Uganda is generally low, attributed to infertile and highly weathered soils in different parts of the country. To increase soil fertility, smallholder farmers are encouraged to adopt integrated soil fertility management (ISFM) practices. Notably, previous studies shown low adoption intensity of ISFM practices. The study, therefore, aimed to determine adoption intensity and factors affecting adoption intensity of ISFM practices in new coffee-growing regions of Mid-Northern Uganda. Data were collected from 202 farmers in Oyam and Nwoya districts, using semi-structured questionnaires. Adoption index (AI) and Tobit regression model were used to determine adoption intensity of ISFM practices and their determinants, respectively. Results show that adoption intensity of ISFM practices was 0.52. Results from Tobit model showed that farm size, access to agricultural insurance, input support, formal employment had positive and significant effect on adoption intensity, whereas household size had inverse and significant effect on adoption intensity. Our study recommends that farmers be trained on ways of accessing credit, agricultural insurance, while government should subsidize farm inputs for timely acquisition by coffee farmers. Publicly Available Content Database